Making crime television: producing entertaining representations of crime for television broadcast - Lam, Anita (Routledge, 2014)
1. Setting the stage : a literature review and analysis -- 2. On method : trail-sniffing ants and breadcrumbs of reflexivity -- 3. Breaking the bridge : documenting the heterogeneous knowledge inputs into the laboratory of the writers' room -- 4. The case of the missing 'bad apples' : transforming 'injured cop' into the 'unguarded moment' -- 5. Showcasing Hamilton : how place becomes relevant in the making of Canadian crime dramas.